PENERAPAN SANKSI TERHADAP LARANGAN MEMBUANG SAMPAH BERDASARKAN PERATURAN DAERAH NOMOR 8 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH DI KOTA PEKANBARU - Nabella Puspa Rani; Rachmad Oky (Jurnal Ilmu Hukum, 2019)
The study aims to explaining the application of sanctions against the prohibition of disposing of waste based on Regional Regulation Number 8 of 2014 concerning Waste Management in the City of Pekanbaru; and analytically critical of the obstacles faced in implementing sanctions against the ban on disposing of waste based on Regional Regulation Number 8 of 2014 concerning Waste Management in the City of Pekanbaru. This type of research is sociological legal research which is more focused on the Policy of Pekanbaru City Government in applying sanctions against the prohibition of disposing of garbage. The results of this study are that the Pekanbaru City Government has not implemented criminal sanctions against the prohibition of disposing of garbage on the streets, in parks and in public places. The administrative sanctions have been made, namely, by giving a warning or making a statement. The obstacle in the application of criminal sanctions is because people who carelessly dispose of garbage cannot afford to pay or the fine is high, which is worth Rp 2,500,000.00 (two million five hundred thousand rupiah).